Exercise Promotes Tissue Regeneration: Mechanisms Involved and Therapeutic Scope - Chang Liu; Xinying Wu; Gururaja Vulugundam; Priyanka Gokulnath; Guoping Li; Junjie Xiao (SpringerOpen, 2023)
Abstract Exercise has well-recognized beneficial effects on the whole body. Previous studies suggest that exercise could promote tissue regeneration and repair in various organs. In this review, we have summarized the major effects of exercise on tissue regeneration primarily mediated by stem cells and progenitor cells in skeletal muscle, nervous system, and vascular system. The protective function of exercise-induced stem cell activation under pathological conditions and aging in different organs have also been discussed in detail. Moreover, we have described the primary molecular mechanisms involved in exercise-induced tissue regeneration, including the roles of growth factors, signaling pathways, oxidative stress, metabolic factors, and non-coding RNAs. We have also summarized therapeutic approaches that target crucial signaling pathways and molecules responsible for exercise-induced tissue regeneration, such as IGF1, PI3K, and microRNAs. Collectively, the comprehensive understanding of exercise-induced tissue regeneration will facilitate the discovery of novel drug targets and therapeutic strategies.